Pagaidu aizsardzība administratīvajā procesā iestādē - Lipkins, Davids (Latvijas Universitāte, 2009)
Maģistra darba izpētes objekts ir pagaidu tiesiskā aizsardzība un pagaidu tiesiskās aizsardzības līdzekļi administratīvajā procesā, it sevišķi pagaidu tiesiskā aizsardzība un pagaidu tiesiskās aizsardzības līdzekļi administratīvajā procesā būvniecības lietās, administratīvo pārkāpumu lietās un Uzņēmumu reģistra lietās. Maģistra darba mērķis ir identificēt problēmas, kas attiecas personu pagaidu tiesisko aizsardzību administratīvajā procesā iestādē, piedāvāt grozījumus normatīvi tiesiskajā regulējumā, kas veicinātu personu pagaidu tiesisko aizsardzību administratīvajā procesā šādās administratīvo lietu kategorijās – būvniecības lietās, administratīvo pārkāpumu lietās un Uzņēmumu reģistra lietās, identificēt minētajās administratīvo lietu kategorijās piemērojamos pagaidu tiesiskās aizsardzības līdzekļus, kā arī piedāvāt spēkā esošo tiesību normu interpretāciju, kas veicinātu personu pagaidu tiesisko aizsardzību administratīvajā procesā. Maģistra darbā tiek analizēti šādi jautājumi, kas saistīti pagaidu tiesisko aizsardzību administratīvajā procesā iestādē būvniecības, administratīvo pārkāpumu un Uzņēmumu reģistra lietās: būvatļaujas darbības apturēšana, Trešo personu tiesības un to ierobežojumi būvniecības lietās, pagaidu tiesiskās aizsardzības līdzekļi administratīvo pārkāpumu lietās, APL regulējuma piemērošana administratīvo pārkāpumu lietās, lēmuma par administratīvo arestu izpildes atlikšana un apturēšana, valsts notāra lēmuma darbības apturēšana un lietvedības apturēšana Uzņēmumu reģistra lietās. Pieminēšu svarīgākos secinājumu pie kuriem nonācis autors pētījuma rezultātā. Analizējot pagaidu tiesisko aizsardzību būvniecības lietās, autors nonācis pie šādiem secinājumiem. Būvatļaujas adresātam jābūt paredzētām tiesībām lūgt tiesu vai augstāko iestādi atjaunot administratīvā akta darbību pirms tiesā ticis iesniegt pieteikums par apstrīdētā administratīvā akta atcelšanu. Analizējot pagaidu tiesisko aizsardzību administratīvo pārkāpumu lietās, autors nonācis pie šādiem secinājumiem. Administratīvo pārkāpumu lietās, kurās lēmumu par soda uzlikšanu atbilstoši LAPK 213.pantam pieņēmis rajona (pilsētas) tiesas tiesnesis nav piemērojama ne administratīvā akta darbības apturēšana, ne pagaidu noregulējums. Tādējādi secina, ka normatīvais regulējums, kad lēmumu par administratīvo arestu izpilda nekavējoties pēc tā pieņemšanas un apelācijas sūdzības iesniegšana neaptur minētā lēmuma izpildi prima facie ir pretrunā ar Satversmes 92. un 94.pantu un Eiropas Cilvēktiesību un pamatbrīvību aizsardzības konvencijas 5.panta pirmās daļas „a” apakšpunktu. Analizējot pagaidu tiesisko aizsardzību Uzņēmumu reģistra lietās, autors nonācis pie šādiem secinājumiem. Uzņēmumu reģistra galvenajam valsts notāram vai vispārējās jurisdikcijas tiesām, būtu piešķirama iespēja lemt par pieņemtā Uzņēmumu reģistra valsts notāra lēmuma darbības apturēšanu, kamēr nav pārbaudīti sabiedrības lēmuma faktiskie apstākļi vispārējās jurisdikcijas tiesā. Likumā „Par Latvijas Republikas Uzņēmumu reģistru” jāveic grozījumi, ieviešot tiesību normu, kas paredz kā pagaidu tiesiskās aizsardzības līdzekli Uzņēmumu reģistra lietās - civilprocesuālo prasības nodrošināšanu.

The Master Paper provides a research on provisional measures of legal protection in an administrative legal action, provisional legal protection and provisional measures of legal protection in an administrative legal action in construction issues, cases of administrative offences and in matters of the Enterprise Register in particular. The aim of the Master Paper is to identify problems related to the provisional legal protection of persons in an administrative legal action in institutions, offer amendments in the normative legal regulation that would promote provisional legal protection of persons in administrative legal actions in the following categories of the administrative cases – construction cases, cases of administrative offences and cases of the Enterprise Register, identify applicable provisional legal protection measures in the categories of the administrative cases mentioned above, an also offer the interpretation of the effective legal regulations that would enable provisional legal protection in an administrative case. The Master Paper provides the analysis of the following issues related to the provisional legal protection in an administrative legal action in institutions in the cases of construction, administrative offences and Enterprise Register: suspension of the building licence, the rights of the third parties and the infringement of these rights in construction cases, provisional legal protection measures in the cases of administrative offences, application of Law on Administrative Offences regulation in the cases of administrative offences, suspension and halting of the ruling on the execution of an administrative arrest, suspension of the implementation of a resolution of a state notary and the suspension of record-keeping in the cases of the Enterprise Register. The following most relevant conclusions gained in the process of the research are to be mentioned. On analysing provisional legal protection in construction cases, the author concluded the following: the beneficiary of the building licence must be provided rights to appeal the court or the highest institution for the restoration of the implementation of the administrative legal act before an application on the cancellation of the litigated administrative legal act has been presented. On analysing provisional legal protection in the cases of administrative offences, the author concluded the following: in the cases of administrative offences, in which the ruling on the infliction of penalty was made by a judge of a regional (municipal) court in compliance with the clause 213 of Code of Administrative Offences of Latvia, nor suspension of an administrative legal act neither provisional regulation can be applied. Therefore the conclusion is that a standard regulation when a ruling on the administrative arrest is executed immediately after it has been made, and the appeal does not suspend the prima facie execution of the ruling mentioned above, is in conflict with the clauses 92 and 94 of the Constitution and the subclause “a” of the first part of the clause 5 of the European Convention for the Protection of Human Rights and Fundamental Freedoms. On analyzing provisional legal protection in the Enterprise Register cases, the author concluded the following: the principal state notary of the Enterprise Register or general jurisdiction courts must be conferred a right to make rulings on the suspension of the activity of the ruling made by the state notary of the Enterprise Register, until the actual conditions of the organization’s ruling are verified at the general jurisdiction court. The amendments to the Law on the Enterprise Register of the Republic of Latvia should be made to introduce legal regulations providing for an bringing a suit as provisional legal preventive means in the Enterprise Register cases.
Provisional measures of legal protection in an administrative legal action
Keywords: Juridiskā zinātne